2021
DOI: 10.1177/0706743721989158
|View full text |Cite
|
Sign up to set email alerts
|

Overall and Gender-specific Associations between Dimensions of Adverse Childhood Experiences and Mental Health Outcomes among Homeless Adults: Associations Générales et Sexospécifiques Entre les Dimensions des Expériences Défavorables de L’enfance et les Résultats de Santé Mentale Chez les Adultes Sans Abri

Abstract: Objective: The associations between adverse childhood experiences (ACEs) and psychopathology have been well-established in the general population. Research on ACEs in the homeless population has been limited. This study examined whether ACE exposure is associated with specific mental health outcomes among a national sample of homeless adults with mental illness and whether this association varies according to ACE dimension and gender. Methods: This cross-sectional study utilized data from a national sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…60 One possible explanation is that both criminal justice involvement and ACEs are risk factors for homelessness, thereby modifying the associations that are observed among the homeless population. 61 Blankertz et al (1993) 53 Bymaster et al (2017) 43 Dawson-Rose et al (2020) 34 Edalati et al (2016) 41 Ferguson et al (2009) 54 Larkin et al (2012) 48 Lee et al (2017) 44 Liu et al (2021) 57 Middleton et al (2018) 49 Mounier et al (2003) 45 Munoz et al (2019) 37 Narayan et al (2017) 35 Narendorf et al (2020) 39 Pluck et al (2011 Edalati et al (2016) 41 Ferguson et al ( 2009) 54 Forde et al (2012) 55 Greeson et al (2019) 52 Koegel et al (1995) 30 Larkin et al (2012) 48 Lee et al (2017) 44 Liu et al (2021) 57 Middleton et al (2018) 49 Mounier et al ( 2003) 45 Munoz et al (2019) 37 Narayan et al (2017) 35 Narendorf et al (2020) 39 Pluck et al (2011) 33 Putnam-Hornstein et al (2017) 50 Another important finding is that most ACE studies among homeless adults were done in Canada or the USA. The disproportionate representation of ACE studies from North America was also reported in another review of homeless adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 One possible explanation is that both criminal justice involvement and ACEs are risk factors for homelessness, thereby modifying the associations that are observed among the homeless population. 61 Blankertz et al (1993) 53 Bymaster et al (2017) 43 Dawson-Rose et al (2020) 34 Edalati et al (2016) 41 Ferguson et al (2009) 54 Larkin et al (2012) 48 Lee et al (2017) 44 Liu et al (2021) 57 Middleton et al (2018) 49 Mounier et al (2003) 45 Munoz et al (2019) 37 Narayan et al (2017) 35 Narendorf et al (2020) 39 Pluck et al (2011 Edalati et al (2016) 41 Ferguson et al ( 2009) 54 Forde et al (2012) 55 Greeson et al (2019) 52 Koegel et al (1995) 30 Larkin et al (2012) 48 Lee et al (2017) 44 Liu et al (2021) 57 Middleton et al (2018) 49 Mounier et al ( 2003) 45 Munoz et al (2019) 37 Narayan et al (2017) 35 Narendorf et al (2020) 39 Pluck et al (2011) 33 Putnam-Hornstein et al (2017) 50 Another important finding is that most ACE studies among homeless adults were done in Canada or the USA. The disproportionate representation of ACE studies from North America was also reported in another review of homeless adults.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative summary of associations is reported in table 4, broken down by definition of ACE exposure, significance of associations, and direction of associations. Of outcomes that were assessed by two or more studies, ACE exposure was consistently associated with high suicidality, 31,57 past suicide attempt, 39,44,47 major depressive disorder, 44,57 substance misuse, 29,39 and adult victimisation in all studies that evaluated ACE exposure and these outcomes. 36,41 Many studies reported no association between ACE exposure and involvement in the criminal justice system as an adult among homeless adults.…”
Section: Table 2: Quality Assessment Of Included Articlesmentioning
confidence: 99%
“…Several studies have examined gender differences in ACEs. Some have found the effects of ACEs, particularly household challenges, on certain mental health outcomes to be stronger for male than female participants ( 25 ), while others suggested ACEs to be more harmful to females ( 50 ). Still, others have found no gender differences in psychological outcomes ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The moderation effect of gender on the relationships among ACEs, resilience, and psychological well-being may manifest in several perspectives. First, the prevalence of ACEs could vary across different gender groups ( 25 , 48 ). For instance, a national survey of 17-year-olds in the U.S. estimated that over one quarter (26.6%) of the female participants had a lifetime history of child sexual abuse, compared to 5.1% of the male counterparts ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation